Uma abordagem geométrica para princípios de localização de integrais funcionais - Dias, M. A [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
We present in this dissertation a conceptual review of diﬀerential geometry, where we are interested in deﬁning vector ﬁelds which are one-parameter transformation generators, diﬀerential forms, symplectic manifolds, and ﬁber bundles. In addition, we detail the concept about De Rham's cohomology, which provides us a fundamental algebraic tool to analyze topological properties of manifolds. The combination of these concepts, which are the background material of our work, allows us to develop equivariant localization theories of integrals deﬁned on classical phase spaces, which can also be a co-adjoint orbit. The localization is possible because of the Duistermaat-Heckman theorem, which allows us to write integrals on the whole space just as a sum, or integral, on a critical points set. Further more, we do an extension to functional integrals localization theories, where it is needed to deﬁne loop spaces. In this context we apply equivariant localization formulation having the bases of Atiyah-Witten conjecture to supersymmetric theories, where we derive the Atiyah-Singer index theorem for a Dirac operator. The index theorem is applied to chiral anomaly calculation

Apresentamos nesta dissertação uma revisão dos conceitos de geometria diferencial, onde estamos interessados em deﬁnir campos vetoriais que geram transformações de um parâmetro, formas diferenciais, variedades simpléticas e ﬁbrados. Além disso, detalhamos o conceito de cohomologia de De Rham, o qual nos fornece uma ferramenta algébrica fundamental para analisar propriedades topológicas das variedades. A combinação desses conceitos, os quais suportam o nosso trabalho, permite-nos desenvolver teorias de localização equivariante de integrais deﬁnidas sobre espaços de fase clássicos, os quais também podem ser uma órbita co-adjunta. A localização é possível devido ao teorema de Duistermaat-Heckman, o qual nos permite escrever integrais como uma soma, ou integral, sobre o conjunto dos pontos críticos do espaço. Em seguida fazemos uma extensão para teorias de localização de integrais funcionais, onde é preciso deﬁnir o espaço dos loops. Nesse contexto aplicamos a formulação de localização equivariante tendo como base a conjectura de Atiyah-Witten para teorias supersimétricas, onde derivamos o teorema de índice de Atiyah-Singer para um operador de Dirac. O teorema de índice é aplicado no cálculo da anomalia quiral
Keywords: Fisica matematica; Integração funcional; Mathematical physics